A Case of Atypical Adult-onset Tic Disorder. Issue 4 (April 2015) - Colosimo, Carlo
<x xml:space="preserve">Abstract</x> Introduction: The differential diagnosis of adult tic disorder is complex, and several common and uncommon causes have to be taken into consideration. Case Report: A 30-year-old man came to our movement disorders clinic with multiple tics which had begun insidiously about 10 years earlier. No family history was reported, but his 65-year-old otherwise healthy father also had very subtle involuntary movements. A diagnosis of atypical Gilles de la Tourette syndrome was made. However, the neurological and psychiatric symptoms of the patient rapidly progressed over the following 2 years, resulting in increasingly severe involuntary movements and profound mood disorder. Further diagnostic tests were performed, and a genetic screening for Huntington disease revealed 45 repeats of the CAG nucleotide in the IT-15 gene. Conclusion: This case underlines the marked phenotypic variability of Huntington disease at presentation, including the presence of involuntary movements different from chorea and possibility of an apparently sporadic disorder.